Enhancing the Enthusiasm of Blind Students through Set Operation Learning Using Fruits Context: A Lesson Study - Nuraida, Elis Muslimah; Sahanata, Meirisa; Dewi, Fitri Kumala; Rizki, Hedia (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2025)
This research aims to enhance the enthusiasm of blind students in learning set operations using the lesson study approach within the context of fruits. This research is motivated by the challenges of presenting the abstract concept of set operations to blind students, who often require media and teaching methods tailored to their conditions. Lesson study, as a collaborative cycle among teachers, is expected to facilitate the development of effective learning strategies. Meanwhile, fruits were chosen as the context because of their characteristics that are close to students' daily lives and easily accessible through the sense of touch. This research method uses design research adapted to the stages of lesson study: Plan, Do, See, and Redesign. Data collection techniques using observation of student activities and documentation. Data analysis was conducted using descriptive qualitative methods to understand how the use of fruits context in lesson study can enhance the enthusiasm and understanding of blind students in learning set operations. The research results are expected to contribute to the development of inclusive mathematics education for blind students, as well as provide practical recommendations for teachers in implementing lesson study and using learning media that meet the needs of the students.